Magnetic Integrated Multi-Trap Filters Using Mutual Inductance to Mitigate Current Harmonics in Grid-Connected Power Electronics Converters - Maged Al-Barashi; Aicheng Zou; Yongjun Wang; Wei Luo; Nan Shao; Zeyu Tang; Bing Lu (Energies)
This paper introduces magnetic integrated high-order trap–trap–inductor (TTL) and inductor–trap–trap (LTT) filters featuring two LC-traps designed for grid-tied inverters, aimed at reducing the size of output-power multi-trap filters. The proposed filters exhibit excellent harmonic absorption capabilities alongside a compact design. Building on the conventional integrated inductor–capacitor–inductor (LCL) filter, the approach involves connecting a small capacitor in parallel with either the inverter-side or grid-side inductors to create an LC trap. Additionally, a second LC trap can be achieved by integrating the filter capacitor in series with the equivalent trap inductance, established by the magnetic coupling between the grid-side inductor and inverter-side one. This paper thoroughly analyzes the characteristics of the proposed filters. Moreover, a design method is presented to further minimize the size of the output filter components. Finally, validation through simulations and hardware-in-the-loop (HIL) experiments confirms the proposed approach’s effectiveness and feasibility. The integrated designs achieve a size reduction of 35.4% in comparison with the discrete windings. Moreover, these designed filters comply with IEEE standards, maintaining a grid-side current total harmonic distortion (THD) of less than 0.9%, with all current harmonics below 0.3% of the fundamental current.